Quality Management of Transport Services: Concept, System Approach, Models of Implementation - Ðšryvoruchko, Oksana; Shynkarenko, Vladimir; Popova, Nadezhda (International Journal of Engineering and Technology, 2018)
The article proposes a conceptual approach to transport services quality management. It is based on the principles of logistical management, management of relationships with consumers, harmonization of the enterprise management system based on the quality and the use of principles of a synergetic systemic approach. The synergetic systemic approach presupposes the formation of a self-organizing quality management system for transport services (cybernetic adaptive, in which the accumulation of experience, the memorization and structuring of information is expressed in a change in the structure of the system and the level of its organization). The scientific novelty of the proposed approach to transport services quality management consists in the integration of the principles of the TQM concept and logistics, the application of a variable approach to selecting technologies for improving the processes of transport and logistics services; comparison of consumer assessment of motor transport services with an evaluation of the quality of processes of its formation. The proposed methodological approach to evaluation takes into account the influence of integrated processes on the final result formation, as well as the effectiveness of each process execution. The implementation of this approach will provide a reasonable choice of methods for providing and improving the quality of transport services, the effectiveness of creating/improving the management system.Â Â